A habilidade de escuta ativa empática do Centro de Ciências Exatas e de Tecnologia da Universidade Federal de São Carlos (UFSCar) - Inácio, Regilene Vieira (Universidade Federal de São Carlos, 2025)
This study investigated the level of development of empathic active listening skills among public servants at the Center for Exact Sciences and Technology of the Federal University of São Carlos (CCET/UFSCar). Empathic active listening is a form of listening motivated by the desire to understand others through active engagement, mindfulness, and empathic comprehension. Techniques associated with empathic active listening skills contribute to improved interpersonal communication, making it a required skill for all public servants. In this context, this study aimed to measure the development of empathic active listening skills among public servants at the Center for Exact Sciences and Technology of UFSCar. To answer the research question and understand the measurement of empathic active listening, an integrative literature review was conducted to identify scales for measuring this skill. This study used the Empathic Active Listening Scale (AELS), a selfreport scale comprising three dimensions: detection, processing, and response, along with the listening skills subscale and the opportunity for conversation from the Active Listening Attitude Scale (ALAS). Data were analyzed using exploratory factor analysis. Statistical analysis of the data showed that the CCET/UFSCar presents a moderate level of empathic active listening skills and that the associations between faculty and administrative staff, and between Engineering and Exact Sciences, show the same level of development. The results of this study demonstrated the importance of empathic active listening in the development of interpersonal communication among public servants and the importance of providing training for the development of empathic active listening in the public service. This study contributed to the literature by studying empathic active listening skills among public servants at a Center for Exact Sciences and Technology of a federal university, filling an academic gap. From a practical standpoint, this research presents an empirical diagnosis of the level of development of empathetic active listening skills among public servants. As a technological product, this study developed a conclusive technical report demonstrating the level of development of public servants at CCET/UFSCar.
The empathic active listening skill of the Center for Exact Sciences and Technology at the Federal University of São Carlos (UFSCar)
Keywords: Escuta ativa empática; Setor público; Soft skills; Comunicação; Empathic active listening; Public service; Communication; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO; 4. Educação de Qualidade